Controlling the porosity of a polyethersulfone membrane surface with an XeCl laser. (3rd February 2016) - Pazokian, Hedieh; Mehrabadi, Adeleh H P; Barzin, Jalal; Mollabashi, Mahmoud
Abstract: Pure and polyvinyl pyrrolidone blend polyethersulfone (PES) membranes were irradiated by an XeCl laser with various numbers of pulses at different fluences to investigate the changes in the surface morphology and the porosity. The results show that the membrane pore size and distribution on the surface can be modified following irradiation dependent on the laser fluence, the number of pulses and the membrane composition. These changes are very attractive for improving the membrane surface in filtration processes and biological applications.